Assessing terrestrial biogeochemical feedbacks in a strategically geoengineered climate. (28th September 2020) - Yang, Cheng-En; Hoffman, Forrest M; Ricciuto, Daniel M; Tilmes, Simone; Xia, Lili; MacMartin, Douglas G; Kravitz, Ben; Richter, Jadwiga H; Mills, Michael; Fu, Joshua S
Abstract: Geoengineering by injecting sulfur dioxide (SO2 ) into the lower stratosphere has been suggested to reduce anthropogenically induced warming. While impacts of such geoengineering on climate have been investigated in recent decades, few modeling studies have considered biogeochemical feedbacks resulting from such intervention. This study comprehensively characterizes responses and feedbacks of terrestrial ecosystems, from an ensemble of coupled high-resolution Earth system model climate change simulations, under the highest standard greenhouse gas scenario with an extreme geoengineering mitigation strategy. Under this strategy, temperature increases beyond 2020 levels due to elevated anthropogenic carbon dioxide (CO2 ) were completely offset by the SO2 injection. Carbon cycle feedbacks can alter the trajectory of atmospheric CO2 levels by storing or releasing additional carbon on land and in the ocean, thus moderating or amplifying climate change. We assess terrestrial biogeochemical feedbacks to climate in response to geoengineering, using model output from the Stratospheric Aerosol Geoengineering Large Ensemble (GLENS) project. Results indicate terrestrial ecosystems become a stronger carbon sink globally because of lower ecosystem respiration and diminished disturbance effects under geoengineering. An additional 79 Pg C would be stored on land by the end of the twenty-first century, yielding as much as a 4% reduction in atmospheric CO2 mole fraction without marine biogeochemical feedbacks, compared to the high greenhouse gas scenario without geoengineering.